Тhe system for analyses of data packages routing in mobile automotive telematics systems - Mnushka, O. V. (My University, 2019)
In the paper, functional requirements for mobile telematics systems are defined. The methods of construction of mobile telematics systems and methods of packet routing in them are analyzed. The structure of a mobile Web-based telematics system based on the use of single-board computers running OS Linux was proposed. The kernel of the server part of the system has been implemented, as well as the integration and communication controller (SCB with SIMCOM modules) too.
Keywords: mobile network; IPv6; NEMO; VANET